Eco-pedagogy in action: transforming primary education for sustainability - Ibrahim, Rini; Yulianto, Ahmad; Faizin, Muh; Rahayu, Desti; Asrul , Asrul; Jaharudin, Jaharudin (Universitas Ahmad Dahlan, 2025)
This study explores the role of primary school teachers in integrating sustainability values into education within an ecologically vulnerable context. It examines how teachers in Sorong City, Southwest Papua, act as agents of change through eco-pedagogical practices, despite facing challenges such as limited training and systemic support. Employing a qualitative case study approach, data were collected through observations, interviews, and document analysis. Findings reveal a gap between teachers' strong ecological awareness rooted in local experiences and their limited understanding of formal sustainability frameworks like the SDGs. While sporadic efforts to integrate environmental themes exist, a systematic, curriculum-aligned approach is lacking. The study highlights the potential for participatory eco-pedagogy to engage students and emphasizes the need for contextualized teacher training and curriculum reform. This research contributes a contextualized pedagogical framework for integrating sustainability values in similar settings globally, advocating for a shift from individual initiatives to structured, reflective, and sustainable educational strategies.